Exploring the link between social axioms and perceived academic control - David, Adonis P. (Philippine Journal of Psychology, 2012)
"This study explored the possible link between five dimensions of social axioms and perceived academic control. Tentative hypotheses were made on the basis of the argument that social axioms that define more personal control over life outcomes will positively predict perceived academic control."